The Challenges of Filling Cases to the International Criminal Court - Baqer Abdulkadhim Ali Al Omar; Amer Sagheer Allwan Al Amery (RIRAI Publisher, 2024)
The International Criminal Court is one of the pillars of the international criminal judicial system that was established according to the Rome Statute with the aim of prosecuting individuals accused of crimes of an international nature according to the jurisdictions that fall under its legal jurisdictional authority. However, the court faces obstacles and problems with regard to submitting and referring cases to the court. The researchers attempt to shed light on some of these problems. The researchers found that the problems are divided into four main categories related to the referrals from signatory states, referrals from non-signatory states, referrals from the United Nations Security Council, and referrals from the Prosecutor of the Court. The researchers presented a number of solutions and suggestions that aim to develop the work of the court and increase its effectiveness to achieve the ultimate goal of achieving justice and protecting victims.